P Pelatihan Desain Grafis menggunakan Canva sebagai Upaya Pemberdayaan Anak Panti Asuhan Muara Kasih Bunda - Iftizam, Syafiranur; Septarita, Femiliana; Eliyani, Marija; Maziidi, Ismail; Jepri, Jepri; Septiani, Dwita Putri; Zaliman, Iski (Universitas Bangka Belitung, 2024)
This research aims to implement the application of the Canva graphic design platform in order to improve the creativity and digital skills of children at the Muara Kasih Bunda Orphanage. The research method used is a case study, with data collection through interviews, observation and documentation. The research results show that using Canva can provide significant benefits for children's orphanages, namely improving visual design skills, opening technological insights, and developing digital skills that are important in the current era. However, there are several challenges such as limited resources, diverse understanding of technology, and the need for intensive guidance and training. This research provides recommendations for orphanages to integrate Canva as part of the educational curriculum, as well as the need for collaboration with various stakeholders to support program sustainability and increase children's orphanage access to technology.